Public relations ethics and professionalism the shadow of excellence - Fawkes, Johanna (Routledge new directions in public relations & communication research, 2015)
This book places PR ethics in the wider context of professional ethics and the sociology of professions. By bringing together literature from fields beyond public relations - sociology, professional and philosophical ethics, and Jungian psychology - it integrates a new body of ideas into the debate. The unprecedented introduction of Jungian psychology to public relations scholarship shifts the debate beyond a traditional Western 'Good/Bad' ethical dichotomy towards a new holistic approach, with dynamic implications for theory and practice.This thought-provoking book will be essential reading for students, academics and professionals with an interest in public relations, ethics and professionalism.